Ответы и объяснения

Лучший Ответ!
  • Voxman
  • главный мозг
2013-04-30T00:11:15+04:00

 

\frac{x+y+3(\sqrt[3]{yx^2}+\sqrt[3]{xy^2})}{\sqrt[3]{x^2}+\sqrt[3]{y^2}+2\sqrt[3]{xy}} = \frac{x+y+3\sqrt[3]{yx}(\sqrt[3]{x}+\sqrt[3]{y})}{(\sqrt[3]{x}+\sqrt[3]{y})^2} =\\\\ \frac{x+y}{(\sqrt[3]{x}+\sqrt[3]{y})^2} + \frac{3\sqrt[3]{yx}(\sqrt[3]{x}+\sqrt[3]{y})}{(\sqrt[3]{x}+\sqrt[3]{y})^2} =\\\\ \frac{(\sqrt[3]{x}+\sqrt[3]{y})(\sqrt[3]{x^2}-\sqrt[3]{x}\sqrt[3]{y}+\sqrt[3]{y^2})}{(\sqrt[3]{x}+\sqrt[3]{y})^2} + \frac{3\sqrt[3]{yx}}{\sqrt[3]{x}+\sqrt[3]{y}} =

 

\frac{\sqrt[3]{x^2}-\sqrt[3]{x}\sqrt[3]{y}+\sqrt[3]{y^2}}{\sqrt[3]{x}+\sqrt[3]{y}} + \frac{3\sqrt[3]{yx}}{\sqrt[3]{x}+\sqrt[3]{y}} = \frac{\sqrt[3]{x^2}-\sqrt[3]{xy}+\sqrt[3]{y^2}+3\sqrt[3]{yx}}{\sqrt[3]{x}+\sqrt[3]{y}} =\\\\ \frac{\sqrt[3]{x^2}+2\sqrt[3]{xy}+\sqrt[3]{y^2}}{\sqrt[3]{x}+\sqrt[3]{y}} = \frac{(\sqrt[3]{x}+\sqrt[3]{y})^2}{\sqrt[3]{x}+\sqrt[3]{y}} = \sqrt[3]{x}+\sqrt[3]{y}

 

Хотя можно было бы так поступить:

 

 

\frac{x+y+3\sqrt[3]{yx}(\sqrt[3]{x}+\sqrt[3]{y})}{(\sqrt[3]{x}+\sqrt[3]{y})^2} = \frac{(\sqrt[3]{x}+\sqrt[3]{y})(\sqrt[3]{x^2}-\sqrt[3]{x}\sqrt[3]{y}+\sqrt[3]{y^2})+3\sqrt[3]{yx}(\sqrt[3]{x}+\sqrt[3]{y})}{(\sqrt[3]{x}+\sqrt[3]{y})^2} =\\\\ \frac{(\sqrt[3]{x}+\sqrt[3]{y})(\sqrt[3]{x^2}-\sqrt[3]{x}\sqrt[3]{y}+\sqrt[3]{y^2}+3\sqrt[3]{yx})}{(\sqrt[3]{x}+\sqrt[3]{y})^2}=

 

\frac{(\sqrt[3]{x}+\sqrt[3]{y})(\sqrt[3]{x^2}+2\sqrt[3]{x}\sqrt[3]{y}+\sqrt[3]{y^2})}{(\sqrt[3]{x}+\sqrt[3]{y})^2}=\frac{(\sqrt[3]{x}+\sqrt[3]{y})(\sqrt[3]{x}+\sqrt[3]{y})^2}{(\sqrt[3]{x}+\sqrt[3]{y})^2}=\sqrt[3]{x}+\sqrt[3]{y}